A common polymorphism in the SCN5A gene is associated with dilated cardiomyopathy. Issue 7 (July 2018) - Mazzaccara, Cristina; Limongelli, Giuseppe; Petretta, Mario; Vastarella, Rossella; Pacileo, Giuseppe; Bonaduce, Domenico; Salvatore, Francesco; Frisso, Giulia
Abstract : Aims: SCN5A is a disease-causing gene associated with familial dilated cardiomyopathy (FDC). We examined the possible association between a common polymorphism in the SCN5A gene (c.1673A>G-p.H558R; rs1805124) and the risk of dilated cardiomyopathy (DCM) occurrence. Methods: We genotyped 185 DCM cases (familial DCM, idiopathic DCM and postischemic DCM) and 251 controls for the p.H558R polymorphism in the SCN5A gene, to test the association of the molecular epidemiology of the individuals with the presence/absence of various types of DCM. Results: Our results showed that the rs1805124 polymorphism was significantly associated with DCM, and the association was more significant in patients with FDC; furthermore, in these individuals, the less frequent GG genotype was associated with a 7.39-fold increased risk of disease [95% confidence interval (95% CI) = 2.88–18.96; P  < 0.0001] compared with the AA genotype. Moreover, logistic regression analysis showed that GG carriers had a higher risk of DCM than AA + AG carriers (odds ratio = 5.45, 95% CI = 2.23–13.35; P  < 0.001). No association was observed between the rs1805124 and DCM risk in postischemic DCM patients. Conclusion: Our study demonstrates an association between familial DCM and the rs1805124 polymorphism in the SCN5A gene, which may unravel additional genetic predisposition to the development of a multifactorial disease as DCM.